If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x + 6) = 5x + 5 Reorder the terms: f(6 + x) = 5x + 5 (6 * f + x * f) = 5x + 5 (6f + fx) = 5x + 5 Reorder the terms: 6f + fx = 5 + 5x Solving 6f + fx = 5 + 5x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Reorder the terms: -5 + 6f + fx + -5x = 5 + 5x + -5 + -5x Reorder the terms: -5 + 6f + fx + -5x = 5 + -5 + 5x + -5x Combine like terms: 5 + -5 = 0 -5 + 6f + fx + -5x = 0 + 5x + -5x -5 + 6f + fx + -5x = 5x + -5x Combine like terms: 5x + -5x = 0 -5 + 6f + fx + -5x = 0 The solution to this equation could not be determined.
| 2x^2+9x+8= | | 5x+4-2=(x+8) | | 6s+(4s-20)=450 | | 7x-3=4-2x | | -6+4(3x-13)=82 | | 2*y-3*y=5 | | 8x+1=1.528 | | -2m-8m=10 | | 24x=24x-27 | | (x+7)2+(y-1)2=32 | | x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 |